2017
DOI: 10.1038/s41598-017-03349-w
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Congenital Hyperinsulinism with ABCC8-Deficient Human Embryonic Stem Cells Generated by CRISPR/Cas9

Abstract: Congenital hyperinsulinism (CHI) is a rare genetic disorder characterized by excess insulin secretion, which results in hypoglycemia. Mutation of sulfonylurea receptor 1 (SUR1), encoded by the ABCC8 gene, is the main cause of CHI. Here, we captured the phenotype of excess insulin secretion through pancreatic differentiation of ABCC8-deficient stem cells generated by the CRISPR/Cas9 system. ABCC8-deficient insulin-producing cells secreted higher insulin than their wild-type counterparts, and the excess insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…CRISPR-Cas9 genome editing [18] has made it possible to efficiently correct specific mutations in order to generate isogenic cell lines that are discordant only for the mutation of interest [19,20]. Differentiating human embryonic stem cells with a K ATP HI mutation in 2D towards beta-like cells has been previously shown to replicate the insulin hypersecretion phenotype in vitro [21].…”
Section: Introductionmentioning
confidence: 99%
“…CRISPR-Cas9 genome editing [18] has made it possible to efficiently correct specific mutations in order to generate isogenic cell lines that are discordant only for the mutation of interest [19,20]. Differentiating human embryonic stem cells with a K ATP HI mutation in 2D towards beta-like cells has been previously shown to replicate the insulin hypersecretion phenotype in vitro [21].…”
Section: Introductionmentioning
confidence: 99%
“…The repression of Kir6.2/SUR1 channels stimulates the release of insulin [60], and it has been reported that mutations and deficiencies of ABCC8 and KCNJ11 induce hyperinsulinism [61][62][63][64][65]. In various studies and clinical reports, the hypersecretion of insulin has been linked to the development of several types of cancer, including breast, colon, liver, and kidney cancers [66,67], and the survival rates through GEPIA in our research also confirmed that higher the expression levels of the two genes, the better is the survival rate ( Figure S4A).…”
Section: Discussionmentioning
confidence: 99%
“…Congenital hyperinsulinism (CHI), a rare genetic disorder related to mutations in sulfonylurea receptor 1 (SUR1), encoded by ABCC8 , is characterized by excessive insulin secretion and hypoglycemia (Nessa et al, 2015 ). ABCC8- deficient sc-β cells recapitulated the disease phenotypes of CHI in vitro , indicating that these cells could be an attractive model for further elucidating SUR1 function (Guo et al, 2017 ). We have summarized the disease models related to islet organoids and sc-β cells in Table 1 .…”
Section: Applications Of Islet Organoidsmentioning
confidence: 99%